Spatiotemporal Distribution of GABAA Receptor Subunits Within Layer II of Mouse Medial Entorhinal Cortex: Implications for Grid Cell Excitability - Berggaard, Nina; Seifi, Mohsen; van der Want, Johannes J. L.; Swinny, Jerome D. (Frontiers in Neuroanatomy, 2018)
GABAergic parvalbumin-expressing (PV+) interneurons provide powerful inhibitory modulation of grid cells in layer II of the medial entorhinal cortex (MEC LII). However, the molecular machinery through which PV+ cells regulate grid cell activity is poorly defined. PV+ interneurons impart inhibitory modulation primarily via GABA-A receptors (GABAARs). GABAARs are pentameric ion channels assembled from a repertoire of 19 subunits. Multiple subunit combinations result in a variety of receptor subtypes mediating functionally diverse postsynaptic inhibitory currents. Whilst the broad expression patterns of GABAAR subunits within the EC have been reported, those expressed by individual MEC LII cell types, in particular grid cells candidates, stellate and pyramidal cells, are less well described. Stellate and pyramidal cells are distinguished by their selective expression of reelin (RE+) and calbindin (CB+) respectively. Thus, the overall aim of this study was to provide a high resolution analysis of the major (α and γ) GABAAR subunits expressed in proximity to somato-dendritic PV+ boutons, on RE+ and CB+ cells, using immunohistochemistry, confocal microscopy and quantitative RT-PCR (qPCR). Clusters immunoreactive for the α1 and γ2 subunits decorated the somatic membranes of both RE+ and CB+ cells and were predominantly located in apposition to clusters immunoreactive for PV and vesicular GABA transporter (VGAT), suggesting expression in GABAergic synapses innervated by PV interneurons. Although intense α2 subunit-immunopositive clusters were evident in hippocampal fields located in close proximity to the EC, no specific signal was detected in MEC LII RE+ and CB+ profiles. Immunoreactivity for the α3 subunit was detected in all RE+ somata. In contrast, only a sub-population of CB+ cells was α3 immunopositive. These included CB-α3 cells which were both PV+ and PV-. Furthermore, α3 subunit mRNA and immunofluorescence decreased significantly between P 15 and P 25, a period implicated in the functional maturation of grid cells. Finally, α5 subunit immunoreactivity was detectable only on CB+ cells, not on RE+ cells. The present data demonstrates that physiologically distinct GABAAR subtypes are selectively expressed by CB+ and RE+ cells. This suggests that PV+ interneurons could utilize distinct postsynaptic signaling mechanisms to regulate the excitability of these different, candidate grid cell sub-populations.